Urban Geomorphological Heritage. An Overview - Reynard, Emmanuel; Pica, Alessia; Coratza, Paola (Quaestiones Geographicae, 2017)
Urbanization is a global phenomenon and currently more than half of the world’s population lives in urban areas. Studies on geomorphological heritage and the development of specific methods of investigation (assessment, inventories, cartography) are, however, relatively rare and limited. This paper first describes the relationships between urbanization and geomorphology. Secondly, it presents an overview of the main works on the urban geomorphological heritage. Then, the main methods of investigation are presented. Finally, we discuss the challenging issues concerning the protection and the promotion of the urban geomorphological heritage.